Cu(II) Ions Adsorption Using Activated Carbon Prepared from Pithecellobium Jiringa (Jengkol) Shells With Ultrasonic Assistance: Isotherm, Kinetic and Thermodynamic Studies - Muslim, Abrar; Ellysa, Ellysa; Said, Syahiddin Dahlan (Journal of Engineering and Technological Sciences, 2017)
Adsorption of Cu(II) ions from aqueous solution onto activated carbon (AC) prepared from Pithecellobium jiringa shell (PJS) waste was investigated by conducting batch mode adsorption experiments. The activation with ultrasound assistance removed almost all functional groups in the PJS-AC, while more cavities and pores on the PJS-AC were formed, which was confirmed by FTIR and SEM analyses. The Cu(II) ion adsorption isotherm fitted best to the Freundlich model with average R2 at 0.941. It was also correlated to the Langmuir isotherm with average R2 at 0.889. This indicates that physical sorption took place more than chemical sorption. The maximum Cu(II) ion adsorption capacity onto the PJS-AC for a dose of 1 g was 104.167 mg/g at 30 °C and pH 4.5, where the Langmuir constant was 0.523 L/mg, the Freundlich adsorption intensity was 0.523, and the Freundlich constant was 5.212 L/mg. Cu(II) adsorption followed the pseudo second-order kinetic (PSOKE) model with average R2 at 0.998, maximum adsorption capacity at 96.154 mg/g, PSOKE adsorption rate constant at 0.200 g/mg.min, temperature at 30 °C and pH at 4.5. The changes in enthalpy, entropy, free energy and activation energy were determined, and the results confirmed that Cu(II) adsorption onto the PJS-AC was exothermic chemical adsorption in part. There was a decrease in the degree of freedom and the adsorption was non-spontaneous.